Office environment and cognitive factors towards health behaviour change intention (HBCI) in banking sector: an extended decomposed theory of planned behaviour (EDTPB) model / Nurul Amyra Mat Isa - Mat Isa, Nurul Amyra (2023)
Although workers represent half of the global population as the major economic and social development catalysts, Malaysian workers reportedly demonstrated poor health habits that impacted employee productivity and organisational loss. The top agenda in the Ministry of Health are driving Malaysia as nation of healthy individual in line with the SDG goals to ensure healthy lives and promote well-being. There is need to understand the complexity behind individual decision and engagement in behavior that affect their health. Having a good theory and intention to change is vital when there is a need for the predicting and understand how and why behavior change. Thus, this study aimed to examine the factors influenced workers’ health behaviour change intention (HBCI)under extended decomposed theory of planned behaviour (EDTPB) model. Based on the central study hypotheses, the HBCI of the workers in the banking sector originated from (i) attitudes towards HBCI, (ii) subjective norms (SN), (iii) perceived behavioural control (PBC), and indoor environmental quality (IEQ). Relative advantage (RA), knowledge (KN), co-worker influence (CWI), mass media(MM), facilitating conditions (FC), and self-efficacy (SE) are incorporated into the model. A total of 250 questionnaires were distributed to the target respondents (bank workers in headquarters and branches) in Selangor, Malaysia following the primary data collection method. The study data were analysed with Statistical Package for the Social Sciences (SPSS) 25.0 and SmartPLS 3.0. As a result, all the proposed sixteen study hypotheses confirmed that eleven hypotheses were positively significant, and five hypotheses were insignificant. The study outcomes highlighted the EDTPB applicability to health behaviour change (HBC) research and suggested useful guidelines and policies for the banking sector to invest in human capital through workplace wellness programmes to achieve a positive return of investment.